2019
DOI: 10.1002/app.47749
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of rubber gel as oil absorbent by using water as porosity agent for oil removal

Abstract: Oil pollution is a crucial issue that has adversed impact not only on the environment but also human beings. As an alternative to all conventional approaches, a porous rubber gel based on liquid natural rubber (LNR) with excellent hydrophobic and wettability properties has been developed using a simple vulcanization reaction. To determine their sorption capability, LNR gel was employed for absorption of various types of oils such as Petrol A, Petrol B, kerosene, diesel, crude oil, and olive oil. The functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Chin et al and Mustapa et al studied natural rubber foam (NRF), which was a promising material for oil spill application to replace the commercial materials. Unfortunately, the results showed that the oil sorption capacity decreased due to the increase in crosslinking agents [ 21 , 22 ]. To improve its effectiveness, a specific material can be added to the NRF as a filler.…”
Section: Introductionmentioning
confidence: 99%
“…Chin et al and Mustapa et al studied natural rubber foam (NRF), which was a promising material for oil spill application to replace the commercial materials. Unfortunately, the results showed that the oil sorption capacity decreased due to the increase in crosslinking agents [ 21 , 22 ]. To improve its effectiveness, a specific material can be added to the NRF as a filler.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been reported to remove oil contaminants from water, such as filtration, 16,17 reverse osmosis, 18 gravity separation, 19 air flotation, 20 ionic flocculation, 21 adsorption, 22 and gel 23 . Among all these methods, the adsorption process is highlighted due to its efficiency, relatively lower processing cost, and simple design 24 .…”
Section: Introductionmentioning
confidence: 99%